GLYCEMIA AND IN THE UMBILICAL VESSELS ACIDUREMIA AND ITS RELATIONSHIP WITH THE NEWBORN APGAR - Palacios Solano, Jesús (2015)
OBJETIVE : To evaluate glycemic and aciduremia in the umbilical vessels at birth and their relationship with the Apgar score DESIGN: Prospective, observational study of double-blind. Location: Regional Hospital of Huacho. MATERIALS AND METHODS: aciduricemia glycemia and umbilical vein and artery of newborns (NB) with normal one minute (RNAN1, n = 44) Apgar and newborns with low Apgar score at one minute (RNAB1, n = 16) was measured whose mothers had received intravenous infusion of sodium chloride 0.9% for labor; the results were statistically associated with Apgar scores of newborns. Glucose was also measured in RNAN1 whose mothers did not receive intravenous infusion (n = 1O). RESULTS: RNAN1 whose mothers received NaCl 0.9% had lower blood sugar than those whose mothers did not receive intravenous infusion, not being statistically significant at the p <0.05 level (p = 0.097). The RABN1 RNAN1 compared with, on average had higher levels of uric acid in the umbilical veins (4.8 ± 1.1mg / dl vs. 4.3 ± 1.4 mg / dL; p = 0.093) and in the umbilical arteries (4.96 ± 0.95 mg / dL vs 4.23 ± 1.28 mg / dL; p = 0.022) in this case being statistically significant at the p <0.05 level. CONCLUSIONS: RNAB1 had a higher average of uric acid in the umbilical arteries compared to RNAN1. With the final catabolite of adenosine triphosphate (ATP) uric acid, the finding suggests that the underlying cause is the low Apgar ATP depletion.